An assessment of knowledge of basic research methods among primary health care workers in Riyadh region - Al-Rossais, Amirah Abdulmohsen; Sayeed, Shibli; Khan, Mohammad Shibly; Al-Qahtani, Malak Ayedh; Fardan, Aedh Nasser Bin (International Journal Of Community Medicine And Public Health, 2021)
Background: The knowledge of and attitude towards medical research among health care staff is an important factor in delivering health care services. We aimed to assess the knowledge of basic research methods and the attitude towards medical research among health care professionals. Methods: A cross-sectional study was conducted among the health care professionals working in primary care (including physicians, nursing staff, public health professionals and other paramedical staff). A pre designed, structured, closed ended, self-administered questionnaire was used to collect the data. Results: A great majority (80%) showed interest in participating in a research if offered opportunity. Most of the attitude items had the highest proportion (>80%) of positive response whereas the knowledge items ranged from as low as 14% (awareness of reference management) to as high as 56% (correct knowledge of consent). Although the proportion of correct responses among the physicians was higher in almost all the knowledge items, as compared to nursing and other heath staff but this difference was not observed to be statistically significant (p>0.05). Conclusions: While majority of the participants had good attitude towards medical research, their knowledge was found to be low in basic research methodology.